EFL chinese students and high stakes expository writing: a theme analysis - Yang, Qian; Ramírez, J. Andrés; Harman, Ruth (Colombian Applied Linguistics Journal, 2007)
The expository essay in English is a key gatekeeping milestone as students seek to move from one level of schooling to the next (Schleppegrell, 2004). Using Systemic Functional Linguistics (SFL), this study analyzes a Chinese college student's expository essay written on a nationwide English examination in China. Two aspects of theme in the textual metafunction will be examined: theme markedness and theme progression (Eggins, 1994; Halliday, 1994). These components are further explored through a parallel analysis of an expository essay written by a North American freshman. This comparative theme analysis highlights areas in pedagogy that should be attended to if EFL students are to get more sophisticated control over important features of expository writing.